Implementasi Metode Dempster-Shafer untuk Diagnosa Defisiensi (Kekurangan) Vitamin pada Tubuh manusia - Yudha Eka Permana; Edy Santoso; Candra Dewi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
In modern times, many people do not pay attention to the intake of nutrients in their daily food cosumption, especially the vitamin content. Vitamin is a complex substance that is needed by our body that serves to help the process of body activities. Vitamin deficiency can lead to an increase in the chances of getting disease in our body and allow the body functions not to work optimally. Checking the level of vitamin deficiency is very rarely done by the community, because it needs a blood test and the cost for the test is quite expensive. In this study the problems are solved by creating an expert system, a system that can diagnose the type of vitamin deficiency in the human body, so it can easily be known which type of vitamin deficiency suffered by the users. This system is implemented using Dempster Shafer method. Testing is done by comparing the conformity of the output of the system to the expert diagnosis. From the test of 30 case data obtained an accuracy of 87%. After testing by increasing the weight value of the symptoms, the accuracy rate increased to 90%. So this expert system can be used to assist users in making a diagnosis of deficiency or vitamin deficiency.